2008
DOI: 10.1590/s1676-06032008000400011
|View full text |Cite
|
Sign up to set email alerts
|

Composição e distribuição vertical de pteridófitas epifíticas sobre Dicksonia sellowiana Hook. (Dicksoniaceae), em floresta ombrófila mista no sul do Brasil

Abstract: Dicksonia sellowiana Hook., a tree fern species, is illegally extracted from the Mixed Ombrophylous Forest of southern Brazil, what changes the vegetation structure and reduces the availability of micro-habitats for epiphytic species. The composition and the vertical distribution of epiphytic pteridophytes were studied on D. sellowiana. The study was carried out in a Mixed Ombrophylous Forest area, at the Parque Municipal da Ronda in the State of Rio Grande do Sul, Brazil. One hundred and sixty four phorophyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 25 publications
6
24
0
7
Order By: Relevance
“…Having characteristic holoepiphytes as the most common epiphyte-phorophyte relationship, as found in the present study, is a pattern commonly reported in studies of fern epiphytes (Labiak & Prado 1998;Schmitt et al 2005;Fraga et al 2008;Schmitt & Windisch 2010;Barros et al 2014) as well as for vascular epiphytes in general (Kersten & Silva 2001;Borgo & Silva 2003;Gonçalves & Waechter 2003;Rogalski & Zanin 2003;Alves et al 2008;Dettke et al 2008;Bataghin et al 2010;Blum et al 2011;Caglioni et al 2012;Staudt et al 2012;Oliveira et al 2013;Barbosa et al 2015, Furtado & Menini Neto 2016. This pattern suggests that most species of epiphytic synusiae possess a set of morphological and physiological adaptations to occupying this environment (Benzing 1990).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Having characteristic holoepiphytes as the most common epiphyte-phorophyte relationship, as found in the present study, is a pattern commonly reported in studies of fern epiphytes (Labiak & Prado 1998;Schmitt et al 2005;Fraga et al 2008;Schmitt & Windisch 2010;Barros et al 2014) as well as for vascular epiphytes in general (Kersten & Silva 2001;Borgo & Silva 2003;Gonçalves & Waechter 2003;Rogalski & Zanin 2003;Alves et al 2008;Dettke et al 2008;Bataghin et al 2010;Blum et al 2011;Caglioni et al 2012;Staudt et al 2012;Oliveira et al 2013;Barbosa et al 2015, Furtado & Menini Neto 2016. This pattern suggests that most species of epiphytic synusiae possess a set of morphological and physiological adaptations to occupying this environment (Benzing 1990).…”
Section: Discussionsupporting
confidence: 88%
“…In a forest with Araucaria in Rio Grande do Sul, Schmitt et al (2005) sampled 40 tree ferns of Dicksonia sellowiana Hook. and found 11 species of epiphytic ferns, while Fraga et al (2008) found 20 fern species on 164 individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trata-se de uma espécie de grande importância ecoló-gica (Senna 1996), não apenas pela grande quantidade de matéria orgânica que pode adicionar ao solo, mas também por abrigar muitas espécies de epífi tas, algumas de forma exclusiva (Sehnem 1978;Cortez 2001;Fraga et al 2008 (Veloso et al 1991), localizadas principalmente na bacia do rio Uruguai e em pequena parte na do rio Iguaçu. O planalto norte está assentado sobre rochas sedimentares do paleozóico e o segmento da área de estudo que se situa para oeste da escarpa da Serra Geral, está sobre as eruptivas mesozóicas, o que condiciona a origem de diferentes tipos de solos (Maack 1968).…”
Section: Introductionunclassified
“…The PNMR has a total area of 1200 ha, covered by areas of grassland and Mixed Ombrophilous Forest (Fraga et al, 2008). Since it is a region of transition between two biomes, the area attracts numerous representatives from the fauna of the Atlantic forest and its associated ecosystems (Fontana et al, 2003).…”
Section: Study Areamentioning
confidence: 99%